Application of Problem-Based Learning to Improve Problem Solving Skills and Creative Thinking Skills of Class XI Students - Ariadna Safitri; Husnul Chotimah; Atok Miftachul Hudha; Abdulkadir Rahardjanto (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
The learning paradigm shift emphasizes the integration of 21st century skills into learning activities. SMAN 4 Malang as a driving school in Malang City has implemented Independent Curriculum in producing students who have the competence and character of the Pancasila Student Profile. The Pancasila Student Profile has relevance to the skills needed in the 21st century. Problem solving skills and creative thinking skills as dimensions of the Pancasila Student Profile are classified into the main abilities that students need to have to face the challenges of the 21st century. However, based on observations of problem-solving skills and creative thinking skills of students in class XI MIPA 3 are still low. Efforts can be made by implementing Problem-based Learning. This study aims to improve problem solving skills and creative thinking skills of XI grade students in Biology learning using Problem-Based Learning. This type of research is a Classroom Action Research which was conducted in two cycles. Each cycle includes planning, implementation, observation, and reflection stages. The research subjects were students of class XI MIPA 3 totaling 31 students. The research data in the form of qualitative data were reduced, grouped, and narrated. Quantitative data were analyzed descriptively inferentially using paired sample t test. The results showed a difference in the average problem-solving skills and creative thinking skills before and after PBL was applied, so this study proves that the application of PBL can improve students' problem-solving skills and creative thinking skills in Biology learning.